Voices of change : race, racism, and colonization in accounting - Lewis, Anton; Saatkamp, Adam J.; Sopt, Joanne (Emerald Publishing Limited, 2025)
This book contains Open Access chapters. Reflection around accounting and race is long overdue. Capturing insights from academics and researchers in the accounting field and connecting them to wider conversations currently taking place, Voices of Change: Race, Racism, and Colonization in Accounting provides an opportunity to open an international dialogue. Voices of Change: Race, Racism, and Colonization in Accounting covers topics ranging from Critical Race Theory - with inclusive representation of theorists recognized by accounting academics - to the decolonization of the accounting curriculum and the role of accounting technologies in contributing to racialized practices in historical contexts. Highlighting present-day struggles across the globe, the chapters presented here are essential reading to those who are interested in diversity and inclusion topics within the accounting industry.
Includes index.
Keywords: Accounting -- History.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books